A Different Approach to Eco Design Perspective for Wind Turbine Transformers - Demir, Caner; Onat, Nevzat; Ates, Yavuz; Metiner, Buse Yagmur; Alemdag, Orkun (IEEE, 2024)
The connection between production capacity and the cost of producing wind turbines is partly due to the economic value of technical equipment. The main components of wind turbines can be classified as the nacelle section (the blades, gear systems and generator located here), tower, foundation, and balance facility components (including transformer and transmission cables). The increase in wind turbine powers in the last 10 years creates new problems in the design and application stages. In transformers that increase in parallel with wind turbine power, the effects of loss costs on the total life cycle cost are reaching remarkable dimensions. This study aims to bring an innovative perspective on the approach outlined in the EN50708 standard which has been recently adopted and is used to determine the level of losses. It has been revealed that it is possible to create more economical options by also taking into account the loading ratio and the activation point of the cooling system for the idle and loaded loss values considered in the transformer efficiency index.
Keywords: ecodesign; efficiency; transformer losses; carbon footprint; sustainability; environmental impact; PEI; LCOE; Energy & Fuels; Engineering